Desenvolvimento e produção das plantas de maracujazeiro-amarelo produzidas por enxertia hipocotiledonar sobre seis porta-enxertos - Filho, Geraldo Costa Nogueira; Roncatto, Givanildo; Ruggiero, Carlos [UNESP]; de Oliveira, João Carlos [UNESP]; Malheiros, Euclides Braga [UNESP] (My University, 2010)
The study was conducted in the ripped and in the area of Fruit of the Department of Plant Production, Faculty of Agricultural and Veterinary Sciences, Universidade Estadual Paulista (FCAV/UNESP), and aimed to assess the development of yellow passion fruit grafted by hypocotyledonary grafting, on six rootstocks of passifloraceas in Jaboticabal-SP. Seven treatments were used, with six treatments and rootstocks: P. edulis, P. caerulea, P. alata, P. gibertii, P. coccinea, P. cincinnata and treatment with non-grafted plants of the P. edulis. For all treatments the crown variety used was the yellow passion fruit plant 'FB 200'. The experimental design used was randomized blocks with 03 repetitions. The plot was formed in a line of four plants (20 linear meters). The conduction was done according to cultural treatments recommended for this culture. The evaluated characteristics were plant height, diameter of the region of grafting, the graft diameter, diameter of the rootstock, relation between scion and rootstock, production, number and average fruit weight. The non-grafted plants showed better development than the grafting ones, and the plants of the rootstock P. caerulea had the worst development. Now the plants of the rootstock P. coccinea showed slower growth, in spite of being quite vigorous.
Development and production of yellow passion fruit produced by hypocotyledonary grafted on six rootstocks
Keywords: Agronomic performance; Passiflora spp.; Vegetative propagation